(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2023)
This study aims to elaborate on Ibn al-Muqaffa’s idea about taqnîn al-ahkâm using the literature review method. Many relevant pieces of primary and secondary literature were analysed using critical analysis techniques. Ibn al-Muqaffa’, who lived during the Abbasid Dynasty, precisely in the time of Abû Ja’far al-Manshûr, had sparked the idea of the legislation of Islamic law (taqnîn al-ahkâm) to be applied throughout the Islamic territory to avoid diverse legal rulings among judges on the same legal case. Re-expressing the idea of Ibn al-Muqaffa’ is important because it has relevance to the ideological ideals of most Indonesian Muslims so that national law absorbs as much as possible from Islamic law. These ideological ideals have grown louder and louder since the freedom of speech in Indonesia has become wide open. As a result, anyone now can express his/her ideological opinions and ideals without any fear of the threat of subversion. In a climate of democracy and freedom, the idea has been resounded again by many groups, including the general public, socio-political activists, academics and parliamentary members.